MAHKAMAH AGUNG, MAHKAMAH KONSTITUSI, DAN URGENSI PEMBENTUKAN PERADILAN KHUSUS PILKADA - maslul, syaifullahil (Universitas Islam Negeri Raden Fatah Palembang, 2019)
The implication of the direct regional head election is the emergence of the results of the Regional Head Election. In the regulation of Law Number 32 of 2004, the results of the Regional Head Election were resolved by the Supreme Court. Through the decision of the Constitutional Court Number 072-073 / PUU-II / 2004 the legislators transferred the authority to the Constitutional Court with the birth of Law Number 22 Year 2007 and Law Number 12 Year 2008. However, the Constitutional Court annulled its authority with issued a decision Number 97 / PUU-XI / 2013. This article explored the resolution of the results of the Election of Regional Heads in the Supreme Court, the Constitutional Court and the discourse on the formation of a special judicial council with the legalized of the Election Law for Governors, Regents and Mayors with a statutory approach. The result of this writing is that as long as there is a final decision in the Supreme Court which is the same as the Permanent Legal Decision, so that it is possible to review the decision of the Supreme Court. In addition, as long as the Constitutional Court deals with disputes over the results of the Regional Head Election, the Constitutional Court settles cases using the sub-justice approach. After the decision 97 / PUU-XI / 2013, the urgency of the formation of special elections for the regional head elections is a necessity by taking into account the 4 elements. First, the establishment of a Special Court under the Supreme Court, second, filling the position of judge, the third special court is in the State Administrative High Court and fourth, the procedural law used is the constitutional court procedural law.